2011
DOI: 10.15258/sst.2011.39.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SSR markers for hybridity and seed genetic purity testing in sunflower (Helianthus annuus L.)

Abstract: The genuineness of a hybrid is one of the most important characteristics of good quality seed. In order to identify pure hybrid and pollen shedders/ offtypes an investigation was performed to identify an ideal SSR marker. 58 primer pairs were screened to identify the specific marker associated with each hybrid and parental lines. Hybrid KBSH-44 could be clearly identified by using ORS 309 and ORS 170, based on the banding pattern resolved on polyacrylamide gel (6%). The complementary banding pattern of both pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In addition to capital invested on hybrid seed production and additional expenditure incurred on storage of hybrid seed, GOT ultimately increases the hybrid seed cost (Nandakumar et al, 2004). Similar to present study, use of SSR markers for genetic purity testing has been demonstrated in rice (Nandakumar et al, 2004); in maize (Wang et al, 2002) and in sunfl ower (Pallavi et al, 2011) and overall data remained comparable with fi eld grow out test. Similar to SSR marker applied in present study with minimum sample size; number of workers with other plants have applied different sample size of seeds for RAPD primers for example: 400 seeds in chicory (Bellamy et al, 1998), 120 in canola (Marshall et al, 1994), 40 in tomato (Rom et al, 1995), 30 in Chinese cabbage (Meng et al, 1998) and 10-20 in pepper (Ballester and Vicente, 1998) to assess the genetic purity of the hybrid seeds.…”
Section: Resultssupporting
confidence: 84%
“…In addition to capital invested on hybrid seed production and additional expenditure incurred on storage of hybrid seed, GOT ultimately increases the hybrid seed cost (Nandakumar et al, 2004). Similar to present study, use of SSR markers for genetic purity testing has been demonstrated in rice (Nandakumar et al, 2004); in maize (Wang et al, 2002) and in sunfl ower (Pallavi et al, 2011) and overall data remained comparable with fi eld grow out test. Similar to SSR marker applied in present study with minimum sample size; number of workers with other plants have applied different sample size of seeds for RAPD primers for example: 400 seeds in chicory (Bellamy et al, 1998), 120 in canola (Marshall et al, 1994), 40 in tomato (Rom et al, 1995), 30 in Chinese cabbage (Meng et al, 1998) and 10-20 in pepper (Ballester and Vicente, 1998) to assess the genetic purity of the hybrid seeds.…”
Section: Resultssupporting
confidence: 84%
“…The 261 varieties represented all types and main cucumber varieties planted in China, including 111 commercial hybrid varieties from the Chinese seed market, 67 varieties from breeders' collections in BVRC, 64 varieties from the Chinese government department, and 19 local landraces from Xishuangbanna of Yunnan Province in China (Supplementary Table S2). Previous studies showed that the genetic purity of hybrid seeds is prone to contamination due to the occurrence of out-crossing with foreign or self-pollinated and physical admixtures 36 . In order to increase the genotype accuracy of each cucumber variety, newly expanded young leaves grown from 30 seeds were used for DNA extraction.…”
Section: Plant Materials and Dna Extractionmentioning
confidence: 99%
“…GOT is time consuming (takes one full growing season for completion), space demanding and often does not allow the unequivocal identification of genotypes. The molecular markers are of great importance for rapid assessment seed purity (Yashitola et al, 2002, Antonova et al, 2006and Pallavi et al, 2011. Rajendrakumar et al (2007) used molecular markers for detection of contaminant in CMS seed stocks of rice and confirm result based on observation recorded in GOT field.…”
Section: Introductionmentioning
confidence: 65%